5-HT2A-mGlu2/3 receptor complex in rat spinal cord glutamatergic nerve endings: A 5-HT2A to mGlu2/3 signalling to amplify presynaptic mechanism of auto-control of glutamate exocytosis. (1st May 2018) - Olivero, Guendalina; Grilli, Massimo; Vergassola, Matteo; Bonfiglio, Tommaso; Padolecchia, Cristina; Garrone, Beatrice; Di Giorgio, Francesco Paolo; Tongiani, Serena; Usai, Cesare; Marchi, Mario; Pittaluga, Anna
Abstract: Presynaptic mGlu2/3 autoreceptors exist in rat spinal cord nerve terminals as suggested by the finding that LY379268 inhibited the 15 mM KCl-evoked release of [ 3 H]D-aspartate ([ 3 H]D-Asp) in a LY341495-sensitive manner. Spinal cord glutamatergic nerve terminals also possess presynaptic release-regulating 5-HT2A heteroreceptors. Actually, the 15 mM KCl-evoked [ 3 H]D-Asp exocytosis from spinal cord synaptosomes was reduced by the 5-HT2A agonist (±)DOI, an effect reversed by the 5-HT2A antagonists MDL11, 939, MDL100907, ketanserin and trazodone (TZD). We investigated whether mGlu2/3 and 5-HT2A receptors colocalize and cross-talk in these terminals and if 5-HT2A ligands modulate the mGlu2/3-mediated control of glutamate exocytosis. Western blot analysis and confocal microscopy highlighted the presence of mGlu2/3 and 5-HT2A receptor proteins in spinal cord VGLUT1 positive synaptosomes, where mGlu2/3 and 5-HT2A receptor immunoreactivities largely colocalize. Furthermore, mGlu2/3 immunoprecipitates from spinal cord synaptosomes were also 5-HT2A immunopositive. Interestingly, the 100 pM LY379268-induced reduction of the 15 mM KCl-evoked [ 3 H]D-Asp overflow as well as its inhibition by 100 nM (±)DOI became undetectable when the two agonists were concomitantly added. Conversely, 5-HT2A antagonists (MDL11, 939, MDL100907, ketanserin and TZD) reinforced the release-regulating activity of mGlu2/3 autoreceptors. Increased expression of mGlu2/3 receptor proteins in synaptosomal plasmamembranes paralleled the gain of function of the mGlu2/3 autoreceptors elicited by 5-HT2A antagonists. Based on these results, we propose that in spinal cord glutamatergic terminals i) mGlu2/3 and 5-HT2A receptors colocalize and interact one each other in an antagonist-like manner, ii) 5-HT2A antagonists are indirect positive allosteric modulator of mGlu2/3 autoreceptors controlling glutamate exocytosis. Graphical abstract: Highlights: Spinal cord glutamatergic terminals possess inhibitory 5-HT2A heteroreceptors. 5-HT2A heteroreceptors colocalize with inhibitory mGlu2/3 autoreceptors. 5-HT2A and mGlu2/3 receptors cross talk in an antagonist-like fashion. 5-HT2A antagonism reinforces the release-regulating activity of mGlu2/3Rs 5-HT2A antagonists are " indirect positive allosteric modulators " of mGlu2/3Rs